Vida urbana: retos y opciones para los pobres en la ciudad - International Food Policy Research Institute (International Food Policy Research Institute, 2004)
Data from many countries show that the concentration of poverty and malnutrition is shifting from rural to urban areas. Although many rural people move to the cities seeking to improve their well-being, they often remain mired in poverty and squalor. Rampant violence, flimsy housing, and filthy living conditions, along with hunger and malnutrition, are becoming the daily lot for more and more people as cities grow. Relatively little is known about the determinants of urban food insecurity and malnutrition, but it is clear that the causes and the actors involved are more diverse and complex in urban settings than in rural ones. IFPRI and its collaborators are studying both the trends in urban food insecurity and manutrition and the causes, which operate at individual, household, and community levels. They are also examining successful urban programs to learn more about how policies and programs can help overcome urban food insecurity and malnutrition. The enormous demographic shift now taking place in developing countries will have major implications for efforts to reduce poverty, food insecurity, and malnutrition. Over the next two decades 90 percent of population growth in developing countries will take place in the cities and towns. More than half of the population of Africa and Asia will live in urban areas by 2020. More than three-quarters of Latin Americans already do. This Brief focuses on (1) livelihood, food, and nutrition security of the urban poor; (2) Urban diets and food security; (3) Research and policy for urban food security; and, (4) The urban environment and food security.